Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Karyawan pada Kantor Pusat PT. Perkebunan Nusantara IV Medan: Penelitian - Yuli Aisyah Iskandar; Harris Pinagaran Nasution; Muhammad Dalim (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to determine the effect of training on employee performance at the Head Office of PT Perkebunan Nusantara IV Medan. And to determine the effect of work motivation on employee performance at the Head Office of PT Perkebunan Nusantara IV Medan. The research method used is a quantitative research method with an associative approach applied to analyze the relationship between two or more variables. Quantitative research in this study uses primary data by distributing questionnaires to respondents, and then the data is processed using the SPSS application. And then numbers are used to represent quantitative data. The sample was taken using a purposive sampling technique, namely the selection of samples based on previously known population characteristics using certain criteria, the number of samples in this study was 101 people. Then the data was processed using multiple linear regression analysis. The results of the study showed 1. In the Training variable individually or partially, it has a positive and significant effect on Employee Performance at the Head Office of PT Perkebunan Nusantara IV Medan.